Sustainable mobility for reducing carbon emissions in the smart university campus, Huánuco, Peru - Reyna-Gonzalez, Julissa Elizabeth; Echevarría, Cesar Wilfredo Rosas; Pajuelo, María Sara Aguirre; Lázaro-Guillermo, Juan Carlos (Edelweiss Applied Science and Technology, 2025)
This study is motivated by the imperative need to preserve and protect the environment. Within this framework, the proposal is to implement a comprehensive sustainable mobility program that will significantly reduce carbon dioxide (CO2) emissions and, in turn, contribute to improving air quality in the city of Huánuco, Peru. The objective was to reduce CO₂ emissions and decrease particulate matter in the air. The study was based on a mixed approach, where both quantitative and qualitative data analysis techniques proved to be valuable in data collection. For air quality monitoring, a portable device was used to measure key pollutants such as CO₂, PM2.5, and PM10 in areas near the university campus (Cayhuayna Oval). Fluctuations in CO₂ concentration were identified throughout the day, indicating possible variations depending on traffic and weather conditions. For simulation and modeling, ArcGIS environmental simulation software was employed, leading to the conclusion that the reduction of fine particles had a positive impact on the health of the university community. From our position as educators, we have observed and understood the growing need to act to mitigate the environmental impact within our university community, committing to an approach that promotes positive and lasting change.